A randomised trial comparing mesalazine and prednisolone foam enemas in patients with acute distal ulcerative colitis. Issue 2 (February 1996) - Lee, F I; Jewell, D P; Mani, V; Keighley, M R; Kingston, R D; Record, C O; Grace, R H; Daniels, S; Patterson, J; Smith, K
Abstract : Distal ulcerative colitis can be treated with oral or rectal mesalazine, or both. A foam enema preparation has been developed and its efficacy investigated. The aim of this study was to evaluate the efficacy and safety of mesalazine foam enemas compared with prednisolone foam enemas in the treatment of patients with acute distal ulcerative colitis. Patients aged over 18 years presenting with a relapse of distal ulcerative colitis were randomly allocated treatment with mesalazine foam enema (n = 149 evaluable patients) and prednisolone foam enema (n = 146 evaluable patients) for four weeks. A randomised multicentre investigator blind parallel group trial was conducted. It was found that after four weeks of treatment, clinical remission was achieved by 52% of mesalazine treated patients and 31% of patients treated with prednisolone (p < 0.001). There was a trend in favour of more patients in the mesalazine group achieving sigmoidoscopic remission (40% v 31%, p = 0.10). Histological remission was achieved by 27% and 21% of patients receiving mesalazine and prednisolone respectively. Symptoms improved in both treatment groups. Significantly more mesalazine patients had no blood in their stools after four weeks of treatment (67% v 40%, p < 0.001). Prednisolone treated patients had significantly fewer days with liquid stools than mesalazine patients, with a median of 0 and 1 days respectively by week 4 (p = 0.001). In this study mesalazine foam enema was superior to prednisolone foam enema with regards to clinical remission, this was supported by favourable trends in sigmoidoscopic and histological remission rates. Both treatments were well tolerated.